Failure mechanism during incremental sheet forming of a commercial purity aluminum alloy. (April 2023) - Kumar, Abhishek; Mehtani, H.K.; Shrivastava, Amber; Mishra, Sushil; Narasimhan, K.; Samajdar, Indradev
Highlights: Microstructural studies reveal failure occurs due to non-uniform deformation during ISF process and leads to necking before fracture. Dislocation density increases with the increase in cone wall angle, a sharp increase in GND was observed near the crack in the cone. Through thickness strain gradient and tensile residual hydrostatic stress trigger the failure in ISF. The role of residual hydrostatic stress on failure was validated by the finite element analysis results. Abstract: Incremental sheet forming (ISF) is known for many advantages over conventional forming, such as part flexibility, low tooling cost and higher formability. Previously various studies have explored the failure mechanism experimentally and numerically. However, limited studies have been performed on the micro-mechanics of failure during ISF process. This study involves failure mechanism during incremental sheet forming of a commercial purity aluminum alloy (AA1050). During experiments, failure (fracture) was observed in truncated cone specimens by increasing the wall angle from 71° to 72°. The mechanism behind failure was explored with detailed microstructural characterization and finite element (FE) simulations. Various samples were taken from the successfully formed and failed cones for microstructural analysis. The electron backscatter diffraction (EBSD) based microtexture measurements associate this failure with more grain fragmentation and necking or localized deformation in the failed cone. Further, the X-ray diffraction (XRD) based residual stress measurements indicate high positive (tensile) hydrostatic stresses (∼157 MPa) on the outer surface of the failed (fractured) cones. Finite element analysis (FEA) with Gurson-Tvergaard-Needleman (GTN) damage model was used for fracture prediction. The FEA results also support the residual hydrostatic stress evolution in the cones, albeit at a slightly different wall angle. Based on microstructural and finite element analysis it is concluded that deformation becomes inhomogeneous when the failure occurs during ISF process.